2021
DOI: 10.5603/ep.a2021.0063
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal “nonadenoma” — clinical characteristics and risk of malignancy

Abstract: Introduction:There is an increasing number of adrenal tumours discovered incidentally during imaging examinations performed for many different indications. Based on imaging results, it is possible to differentiate benign from malignant adrenal masses, although there is still a number of equivocal imaging findings. Our study presents 77 cases of adrenal tumours in which imaging was inconclusive and the final diagnosis was stated only after surgery and histopathological examination. Material and methods:Retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Additionally, there was no significant correlation between adipocytokines levels and adenoma size. The initial diagnosis based on the computed tomography (CT) scan, despite the possibility of assessing the adrenal tumor imaging phenotype, may be inconclusive, and the final diagnosis requires histopathological examination [ 23 ]. Therefore, increased visfatin levels could be a potential predictor of tumor malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there was no significant correlation between adipocytokines levels and adenoma size. The initial diagnosis based on the computed tomography (CT) scan, despite the possibility of assessing the adrenal tumor imaging phenotype, may be inconclusive, and the final diagnosis requires histopathological examination [ 23 ]. Therefore, increased visfatin levels could be a potential predictor of tumor malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports provide valuable insights into its clinical presentation, diagnostic challenges, and therapeutic outcomes. Zhou et al and Wei et al contributed to the literature with a comprehensive literature review, emphasizing the importance of integrating clinical, radiological, and histopathological findings for accurate diagnosis and optimal treatment planning [5,25,29,31,37,40,43,46,47,56]. Zetler et al reported a case in an AIDS patient, suggesting a potential link between immunocompromised states and leiomyosarcoma [12].…”
Section: Demographic Featuresmentioning
confidence: 99%